2020
DOI: 10.1016/j.ecoenv.2020.110784
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mechanisms involved in tolerance and accumulation of Cd in Biscutella auriculata L

Abstract: Biscutella auriculata L. is one of the rare species that is able to grow in a very contaminated mining area in Villamayor de Calatrava (Ciudad Real, Spain). In an effort to understand the mechanisms involved in the tolerance of this plant to high metal concentrations, we grew B. auriculata in the presence of 125 μM Cd(NO3)2 for 15 days and analysed different parameters associated with plant growth, nitric oxide and reactive oxygen species metabolism, metal uptake and translocation, photosynthesis rate and biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 115 publications
1
8
0
Order By: Relevance
“…The analysis of SOD activity through native‐PAGE showed four isoforms in control leaves, while in those with Cu treatment three of them had almost disappeared (Figure 4). The same phenomenon was observed in this species in response to Cd, which could indicate the low contribution of SOD to the mechanism of Cu and Cd tolerance in B. auriculata (Peco, Higueras, et al, 2020), while in plants exposed to Pb a considerably induction of all isoforms were observed (Peco, Campos, et al, 2020), suggesting mechanistic differences depending on the type of metal. Several evidences demonstrate changes in SOD activity depending on the Cu concentration in different plant species; low doses produced an increment in SOD activity in Boehmeria nivea and Withania somnifera , while high doses resulted in a reduction of this activity (Rout et al, 2013, Hakeem et al, 2019).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The analysis of SOD activity through native‐PAGE showed four isoforms in control leaves, while in those with Cu treatment three of them had almost disappeared (Figure 4). The same phenomenon was observed in this species in response to Cd, which could indicate the low contribution of SOD to the mechanism of Cu and Cd tolerance in B. auriculata (Peco, Higueras, et al, 2020), while in plants exposed to Pb a considerably induction of all isoforms were observed (Peco, Campos, et al, 2020), suggesting mechanistic differences depending on the type of metal. Several evidences demonstrate changes in SOD activity depending on the Cu concentration in different plant species; low doses produced an increment in SOD activity in Boehmeria nivea and Withania somnifera , while high doses resulted in a reduction of this activity (Rout et al, 2013, Hakeem et al, 2019).…”
Section: Resultssupporting
confidence: 61%
“…Although there are few studies in which the accumulation of PC in response to Cu has been found, it has been well documented that this is a general response to other metals such as cadmium (Peco, Higueras, et al, 2020; Wojas et al, 2010). In B. auriculata cadmium induced both PC2 and PC3 in roots and leaves (Peco, Higueras, et al, 2020), while lead only induced PC2 in roots (Peco, Campos, et al, 2020), demonstrating a metal‐dependent specific regulation of PCs synthesis. The mechanism of the action of PCs has been described for Nicotiana tabacum plants in response to cadmium, in which PCs form complexes with the metal in the cytosol and these are actively transported into the vacuole (Wojas et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more attention must be paid to plants metabolism and molecular mechanisms to reveal the direct role of organic amendments, such as biochar, in future phytoremediation studies, as pointed out by Liu et al [50]. For example, the recent study of Peco et al [51] has found Biscutella Control SGB PLB auriculata L, a wild herbaceous species that grows on pastureland, as a new Cd-tolerant plant capable of activating efficient metal-sequestering mechanisms in the root surfaces and leaves, and of inducing phytochelatins in both parts, besides stimulating antioxidative defenses in roots.…”
Section: Discussionmentioning
confidence: 99%
“…According to similar studies on stoma and epidermal hairs (for 1 mm 2 leaf surface); in after the applications of 0 and 125 μM Cd [68]. This could be a response for survival of the plant in applied Cd concentrations, with increased stomata and epidermal hair numbers even when the plant is under stress.…”
Section: Resultsmentioning
confidence: 71%